Hospital-based study of methicillin-resistant Staphylococcus aureus in surgical site infections with special reference to determination of environmental and human sources - Bhave, Poorva P.; Ramteerthakar, Meena N.; Kartikeyan, S.; Patil, Nilima R. (International Journal of Research in Medical Sciences, 2016)
Background: Surgical site infection (SSI) due to methicillin-resistant Staphylococcus aureus (MRSA) is associated with increased morbidity and mortality. Carriage of MRSA by healthcare personnel is a potential source for SSI. The present study was carried out to study the frequency of MRSA in SSI; to identify the most suitable identification test for routine use; and to determine the environmental and human source of MRSA. Methods: In this prospective study, 195 SSI-pus samples were processed for primary staining, culture and biochemical tests. Cefoxitin and oxacillin disc diffusion test and oxacillin broth dilution test were used to detect MRSA and to determine the minimum inhibitory concentration (MIC) among the identified S. aureus. Environment was sampled periodically using air settle plates and swabs from various sites. Healthcare personnel were screened for nasal and hand carriage of MRSA. Results: Of the 205 isolates, 46 were S. aureus, and among these, 18 strains were MRSA. There was no discrepency in the result by any of the three methods used. MRSA carriage, found on the hands of three healthcare personnel, had same anti-biogram as those strains simultaneously obtained from the patients. All three personnel responded to Mupirocin treatment. No MRSA was obtained from the environment. Conclusions: MRSA is an important source of SSI. Cefoxitin disc diffusion method seems suitable technique for routine use. Periodic screening of healthcare workers for carriage of MRSA will prevent outbreaks of nosocomial infections.